OPTIMALISASI GURU DALAM PELAKSANAAN PEMBELAJARAN TATAP MUKA TERBATAS PADA MASA PANDEMI DI SMPN 2 KINTAP KABUPATEN TANAH LAUT - Meriyanti Meriyanti (PROCEEDING UMSURABAYA, 2022)
The Covid-19 pandemic has put the world of education in a state of concern. After online learning has been carried out for approximately two years, the government has again distributed circulars to conduct face-to-face learning on a limited basis so that students can attend schools to meet face-to-face learning with teachers but still adhere to health protocols and with restrictions on learning time. This study aims to determine and describe how to optimize teachers in face-to-face learning during the pandemic. This study uses a qualitative method that is field research located at SMPN 2 Kintap, Tanah Laut Regency. Informants in this study were teachers and students. While the data collection used through interviews, observation, and documentation. The validity of the research data was carried out by member checking, namely asking the informants from the results of interviews that had been conducted to be strengthened and corrected. While the data analysis techniques with data reduction, data presentation, and verification or drawing conclusions. The findings of this study conclude that the optimization of teachers in face-toface learning during the pandemic, namely: (1) teachers try to provide limited learning materials; (2) teachers use learning strategies and methods so that limited face-to-face learning continues in an orderly and smooth and effective manner; (3) teachers as motivators, and facilitators so that students remain enthusiastic even though faceto-face learning is limited.Â Keywords: Optimization; Limited Face-to-face Learning; Covid-19.